The long road to Stockholm : the story of magnetic resonance imaging - an autobiography - Mansfield, P. (Oxford : Oxford University Press, 2013)
In this autobiography, Sir Peter Mansfield describes his life from his early childhood in war time London to his research in nuclear magnetic resonance and the development of magnetic resonance imaging. For his discoveries in MRI, Sir Peter was awarded the 2003 Nobel Prize for Medicine, shared with Paul Lauterbur.
Includes index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Mansfield, P; Scientists -- Great Britain -- Biography; Nobel Prize winners -- Great Britain -- Biography; Magnetic resonance imaging -- History